SCIENTIFIC RESEARCH IN MANAGEMENT ACCOUNTING IN THE ENANPADs FROM 2003 TO 2008 - Araújo, Elisson Alberto Tavares (2010)
The objective of this work is to know some bibliometrics aspects of Management Accounting (MA) in the EnANPADs from 2003 to 2008. In this empirical research 251 articles were analyzed based on the model of Shields (1997). To do so, descriptive statistical methods were used, besides the application of the law of Lotka. It was verified that the Brazilian authors follow the trend of replying the international studies in MA, in which the subject Management Control System (MCS) was predominant. These authors have explored more the new areas of the MA, corroborating Faro and Silva (2008) and Shields (1997). Women have extended their interest for the research in MA. It was perceived that an abandonment of the individual research has occurred, perhaps due to the pressure of CAPES for publications. The own articles of the authors were mentioned few times to base their later research, something distinct of what the international researchers do. Finally, with the estimated coefficient above Lotka's standard, it can be said that MA Brazilian authors do not publish with effectiveness in the EnANPAD, either due to the severity in the evaluation or because some of them only publishes works deriving of dissertations and thesis, not becoming acting researchers. Then, it was concluded that apparently there is a lack of scientific research in MA in the EnANPADs.